Behavior of a scaled‐down scrubber for the removal of H2S from the gases of an upflow anaerobic sludge blanket reactor - Acaro, José (2017)
The present work reports the simulation of a wet scrubber coupled to an UASB reactor. The scrubber consisted of baffles, packed bed of sponge material, an acrylic tube and all the connections necessary to bring the H2S‐ladden biogas. The purpose of the equipment is to eliminate some of the gases coming out of the reactor, through their oxidation by the dissolved oxygen provided by the microalgae present in the water from the tertiary lagoon. Hydrogen sulfide is a foul‐ smelling and toxic gas which can cause death at high concentrations, and can also cause damage to the structures with which it comes into contact. The scrubber was installed on the site of CITRAR‐UNI and the behavior of the equipment was monitored during three weeks by following the temperature, pH and the concentrations of sulfates and dissolved oxygen. The results have shown that the scrubber was effectively an oxidizing environment which was removing H2S, since the dissolved oxygen was actually consumed gradually. It was also observed that the sulfate concentration was increasing, indicating a consumption of H2S, which was also confirmed by a reduction in the odor of the gas.